Potensi Bakteri Endofit Dalam Menekan Pertumbuhan Phytophthora Palmivora (Butler) Secara In Vitro - FOEH, SUSAN CAMILA; TEMAJA, I GEDE RAI MAYA; KHALIMI, KHAMDAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.4, Oktober 2019, 2019)
Potential of Endophytic Bacteria in Suppressing The Growth of Phytophthora palmivora (Butler) in Vitro The purpose of this study was to determine the potential of endophytic bacteria in controlling cocoa fruit rot caused by the fungus Phytophthora palmivora. The study was conducted in vitro and direct test on cocoa fruit. The results of the inhibitory test showed that 4 isolates of endophytic bacteria had the best inhibition for suppressing the growth of Phytophthora palmivora. The in vitro inhibitory test showed, the treatment of TN41 isolates was able to inhibit Phytophthora palmivora with the highest inhibition percentage of 92.52% when compared to the control at the observation of 5 days after inoculation. The direct test on cocoa fruit showed the treatment of TN41 isolate had the least area of spot that is 0.20 mm 2 at 7 days after inoculation. Further research needs to be conducted related to the stability of endophytic bacteria isolate TN41 as an antagonist agent against Phytophthora palmivora.